2011
DOI: 10.1016/j.ygcen.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and expression of β1-, β2- and β3-adrenergic receptors in the fathead minnow (Pimephales promelas)

Abstract: Complimentary DNAs for three beta-adrenergic receptors (βARs) were isolated and characterised in the fathead minnow. The encoded proteins of 402 (β(1)AR), 397 (β(2)AR) and 434 (β(3)AR) amino acids were homologous to other vertebrate βARs, and displayed the characteristic seven transmembrane helices of G Protein-coupled receptors. Motifs and amino acids shown to be important for ligand binding were conserved in the fathead minnow receptors. Quantitative RT-PCR revealed the expression of all receptors to be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…) and of the fathead minnow ( Pimephales promelas ) (Giltrow et al . ). In fathead minnow, β 3 ‐ARs showed the highest expression in the heart, followed by liver, ovary, brain, gills, red blood cells and adipose tissue (Giltrow et al .…”
Section: Effects On Cardiac Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and of the fathead minnow ( Pimephales promelas ) (Giltrow et al . ). In fathead minnow, β 3 ‐ARs showed the highest expression in the heart, followed by liver, ovary, brain, gills, red blood cells and adipose tissue (Giltrow et al .…”
Section: Effects On Cardiac Functionmentioning
confidence: 97%
“…In fathead minnow, β 3 ‐ARs showed the highest expression in the heart, followed by liver, ovary, brain, gills, red blood cells and adipose tissue (Giltrow et al . ). In amphibians, to the best of our knowledge, only Mazza et al .…”
Section: Effects On Cardiac Functionmentioning
confidence: 97%
“…We found that freshwater sticklebacks have higher expression of beta-2 adrenergic receptors (adrb2a) in the brain. These receptors are expressed in a variety of tissues in fish, including the brain [Pimephales promelas (Giltrow et al 2011)], but their role in the central nervous system is less studied. Our results uncover a potential new association between this receptor and stress physiology, and suggest that the functional implication of their higher expression in more aggressive, more active, less social and less reactive fish (Di Poi et al 2014, 2016 should be further studied.…”
Section: Functional Implications Of the Differential Regulation Of Prnsmentioning
confidence: 99%
“…Adrenergic pathways and receptors, particularly beta-adrenergic receptors as the phylogenetic older ones, are conserved in fish (Owen et al 2007;Giltrow et al 2011;Fabbri and Moon 2016). Hence, specific receptor-related effects may occur in fish as postulated by the FPM.…”
Section: Introductionmentioning
confidence: 99%